2014
DOI: 10.1111/caje.12069
|View full text |Cite
|
Sign up to set email alerts
|

Fertility, Intra‐Generational Redistribution, and Social Security Sustainability

Abstract: Incorporating heterogeneity in preference to having children into an overlapping generations model of a small open economy, we examine the effects of changes in the size of pay‐as‐you‐go (PAYG) social security on fertility choices of individuals and population growth of the economy. It is shown that PAYG social security will raise population growth by increasing the number of individuals who have children and the number of children parents have if the system involves redistribution between retirees with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…with lumpsum contributions and pensions) reduce fertility. In contrast, Hirazawa et al (2014) show that in a model with specific log-linear utility functions the effect of Bismarckian PAYG pension scheme on fertility vanishes.…”
Section: Institutional Backgroundmentioning
confidence: 75%
“…with lumpsum contributions and pensions) reduce fertility. In contrast, Hirazawa et al (2014) show that in a model with specific log-linear utility functions the effect of Bismarckian PAYG pension scheme on fertility vanishes.…”
Section: Institutional Backgroundmentioning
confidence: 75%
“…The study of FLMA is deemed having a foundational role in the creation of labour economics (Heckman and MaCurdy, 1980). Through these studies, FLMA has been found to be important for economic growth rate (Klasen and Lamanna, 2009;Diebolt and Perrin, 2013), level of development (Tzannatos, 1999;Bandiera and Natraj, 2013), and fiscal sustainability of the welfare state, especially in aging societies (Apps, 1991;Hirazawa et al, 2014). Despite such economic significance, FLMA cannot be regarded as a uniquely economic phenomenon.…”
Section: Introductionmentioning
confidence: 99%